Analisis Produksi dan Efisiensi Alokatif Usahatani Lada di Desa Ameroro Kecamatan Tinondo Kabupaten Kolaka Timur - Nursalam Nursalam (Fakultas Pertanian, Universitas Timor, 2020)
This study aims to analyze the factors that influence the production and efficiency of pepper farming allocations. This research was carried out in Ameroro Village, Tinondo District, East Kolaka Regency, where the location was determined deliberately. This technique takes research samples using simple random sampling and is calculated using the Slovin formula. The number of respondents obtained was 60 households. This research was conducted from December 2018 to April 2019. The type of data analysis used is multiple linear regression and allocation efficiency. The model used is the relationship between the cobb-Douglas production function. The results of this study use simultaneous or together (F test). There is a significant effect on pepper production. With an adjusted R2 value of 0.799. This shows that at 79.9%, pepper production is influenced by land areas (X1), labor (X2), phonska fertilizer (X3), and pesticides (X4). The tukey test shows that the factors of production of land areas, labor, phska fertilizer, and pesticides are very influential on the increase in pepper production. Based on the results of the analysis of the efficiency of production factors: NPMx/Pxis greater than 1, which means it is ineffective, so an increase in the input is needed to produce a more massive output.